2017
DOI: 10.1111/jam.13492
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofBrachyspira hyodysenteriaeisolates from Italy by multilocus sequence typing and multiple locus variable number tandem repeat analysis

Abstract: The genotyping of B. hyodysenteriae isolates and a database of all the genetic profiles collected during the diagnostic activities could support traditional epidemiological investigations in identifying infection sources and routes of transmission among herds, and in developing more effective control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…MLST and MLVA profile results suggest that trucks transporting pigs from a high number of farms may also play a potential role in spreading different B. hyodysenteriae genetic profiles. In general, the same strains isolated in trucks were found in high production areas, as previously reported by Gasparrini and colleagues [ 14 ]. Nevertheless, the role of these trucks in spreading different B. hyodysenteriae strains should be further investigated because one of the limitations of this study is that only one isolate per batch was identified.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…MLST and MLVA profile results suggest that trucks transporting pigs from a high number of farms may also play a potential role in spreading different B. hyodysenteriae genetic profiles. In general, the same strains isolated in trucks were found in high production areas, as previously reported by Gasparrini and colleagues [ 14 ]. Nevertheless, the role of these trucks in spreading different B. hyodysenteriae strains should be further investigated because one of the limitations of this study is that only one isolate per batch was identified.…”
Section: Discussionsupporting
confidence: 82%
“…The STVT 83–3 profile, present in 9 of 16 samples, should be the current dominant type in Italy. In two recent studies, STVT 83–3 represented more than 45% of the B. hyodysenteriae isolates from 2012 to 2015 [ 14 , 21 ]. Notwithstanding the low number of isolated strains from trucks, the strain genetic diversity is high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations